Association of Education and Depressive Symptoms with Tooth Loss. (April 2021) - Fukuhara, S.; Asai, K.; Kakeno, A.; Umebachi, C.; Yamanaka, S.; Watanabe, T.; Yamazaki, T.; Nakao, K.; Setoh, K.; Kawaguchi, T.; Morita, S.; Nakayama, T.; et al.
Previous evidence suggests the association of lower educational attainment and depressive symptoms with tooth loss. The hypothesis of this study was that these factors may exacerbate the effect on tooth loss beyond the sum of their individual effects. We aimed to clarify the independent and interactive effects of educational attainment and depressive symptoms on the number of missing teeth among community residents. Cross-sectional data of 9, 647 individuals were collected from the general Japanese population. Dental examination was conducted by dentists. Educational attainment was categorized into 3 levels based on the number of educational years: ≤9, >9 to ≤12, and >12 y. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to assess depressive symptoms; a total score of ≥16 and/or the use of medications for depression indicate the presence of depressive symptoms. In the multivariate analysis with adjustment for conventional risk factors, educational attainment was identified as a determinant of the number of missing teeth (>9 to ≤12 y of education: coefficient = 0.199, 95% confidence interval [CI], 0.135 to 0.263, P < 0.001; ≤9 y of education: coefficient = 0.318, 95% CI, 0.231 to 0.405, P < 0.001: reference, >12 y of education). An analysis that included interaction terms revealed that the relationship between "≤9 y of education" and the number of missing teeth differed depending on the depressive symptoms, indicating a positive interactive association (coefficient for interaction = 0.198; 95% CI, 0.033 to 0.364, P for interaction = 0.019: reference, >12 y of education). Our study suggests the presence of a significant association between educational attainment and tooth loss, as well as a partial interactive association between "≤9 y of education" and "depressive symptoms" in the general Japanese population.